Nitrites and nitrates in the human diet: Carcinogens or beneficial hypotensive agents?. (5th June 2015) - Butler, Anthony
Abstract: Ethnopharmacological relevance: The presence of nitrite in the human diet was thought to constitute a hazard as secondary nitrosamines are known to cause gastric cancers. Materials and methods: Recent publications on the physiology of serum nitrite have been consulted. Problems: Nitrite is added to some foodstuffs as an antibotulinum agent. Results and Discussion: The epidemiological evidence that nitrite causes gastric ulcers is weak. On the other hand, evidence that the presence of nitrite in serum lowers blood pressure is strong. This allows us to explain why a Tang dynasty treatment for angina, given in a Dunhuang medical manuscript, can be successful. Conclusion: The presence of nitrite in food is free of danger and a diet high in nitrate is beneficial to the health. Graphical abstract: